Barriers to the integrality of care for people with hanseniasis: perception of Nurses (Research, Society and Development, 2020)
Introduction: Leprosy is an infectious disease considered as a Public Health problem. Comprehensive health care for people with this disease is a major challenge today. Objective: To describe the nurses’ perception about the barriers to comprehensive care for people with leprosy. Methods: It is an exploratory-descriptive, qualitative research, conducted at a National Reference Center on Dermatology in Fortaleza-CE, from February to April 2013. Data were collected with seve nurses through an in-depth interview and analyzed according to the Bardin’s content analysis technique. Results: The main category "Leprosy: barriers to the integrality of care according to nurses’ perception" revealed as difficulties of integral care: Difficulties in the early detection of leprosy cases; Ineffective management and coping of disease; and Prejudice as a barrier to integral care. Conclusion: Nurses emphasized the importance of the performance of qualified professionals in Primary Heatlh Care to reach the goal of control and elimination of leprosy, to achieve the goal of leprosy control and elimination, as well as the intersectoral approach to overcome the obstacles that involve the Integrality in Health.